2009
DOI: 10.1161/circulationaha.108.895482
|View full text |Cite
|
Sign up to set email alerts
|

Hyperintense Plaque With Noncontrast T1-Weighted Magnetic Resonance Coronary Plaque Imaging Leading to Acute Coronary Syndrome

Abstract: A 73-year-old diabetic man underwent multislice computed tomography (MSCT) and noncontrast T1-weighted (T1W) magnetic resonance imaging (MRI) for the evaluation of atypical chest discomfort after an exercise ECG was nondiagnostic. The MSCT demonstrated a low-density positive remodeling plaque and spotty calcification without significant stenosis in the proximal segment of the right coronary artery ( Figure 1A and 1B). Noncontrast T1W MRI, using a 1.5-T MR system (Intera, Philips Medical Systems, Best, the Neth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…These HIPs have been observed more frequently in the culprit lesions of ACS patients. 23, 24 In addition, Oei et al reported that these HIPs may correlate with intraplaque hemorrhage and they concluded that this plaque imaging technique may emerge as a valuable tool for detecting "active coronary lesions". 25 On the basis of its ability to provide excellent soft-tissue contrast, MRI appears to be the superior modality for characterizing unstable plaque components.…”
Section: Expectation Of Coronary Magnetic Resonance Imaging (Mri) Detmentioning
confidence: 99%
“…These HIPs have been observed more frequently in the culprit lesions of ACS patients. 23, 24 In addition, Oei et al reported that these HIPs may correlate with intraplaque hemorrhage and they concluded that this plaque imaging technique may emerge as a valuable tool for detecting "active coronary lesions". 25 On the basis of its ability to provide excellent soft-tissue contrast, MRI appears to be the superior modality for characterizing unstable plaque components.…”
Section: Expectation Of Coronary Magnetic Resonance Imaging (Mri) Detmentioning
confidence: 99%
“…The 3D spiral acquisitions with dark blood preparation used to acquire the coronary vessel wall images in this study were proton density weighted and provided no characterization of vessel wall composition. However, several recent studies have partly addressed this (26–29) by performing T1‐weighted imaging pre‐ and postadministration of gadolinium based contrast agent. These additional acquisitions could also be performed with 3D spiral imaging with B2B‐RMC at high respiratory efficiency after only minor modifications to the sequence used here.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a HIP in the carotid arteries predicted cardiac events, outperforming carotid intimal medial thickness and traditional cardiovascular risk factors 60 ) . In the coronary arteries, a case report first described a high-intensity coronary plaque going on to rupture and cause MI 61 ) . HIPs are quantitatively assessed by a plaque-tomyocardium signal intensity ratio (PMR).…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%